Leveraging Digital Finance to Scale the Solar Home Systems Market in Pakistan - World Bank (World Bank, Washington, DC, 2022)
Decentralized solar home systems (SHS), coupled with asset finance, can provide affordable and reliable electricity to the off-grid population in Pakistan and can augment the energy supply where the grid is available but the electricity supply is limited. Pakistan ranks high on the metric of market readiness for SHS technology. In addition, the country has all the underlying system requirements to leverage mobile banking for growing the local SHS market. In 2020, there were 167.3 million cellular mobile subscribers providing mobile phone access to 95 percent of the country’s households. The GSM Association (GSMA) estimates that close to 30 million people, or 14 percent of the total population in Pakistan, is covered by a mobile network before having access to the grid. This brief analysis was compiled by the World Bank to assess the potential for using mobile banking to scale the SHS market in Pakistan. The report explores the synergy between mobile banking services and SHS businesses, and develops a use case for mobile wallets in SHS business models through a case study of the SHS market in Sindh, Pakistan.